Addition of low dose hCG to rFSh benefits older women during ovarian stimulation for IVF - Gomaa Hala; Casper Robert F; Esfandiari Navid; Chang Paul; Bentov Yaakov (BMC, 2012)
Abstract Background To compare the outcome of IVF cycles in women receiving controlled ovarian stimulation with recFSH or recFSH plus low dose hCG. Methods A retrospective case control study, performed at a private practice affiliated with an academic institute. Patients were infertile women who were treated with IVF/ICSI and controlled ovarian stimulation in a long GnRH agonist protocol using either low dose hCG in addition to recFSH [N = 88] or recFSH alone [N = 99]. Primary outcomes were mean FSH dose, number of mature eggs, number of fertilized eggs, and serum levels of estradiol. Secondary outcomes were endometrial thickness, cycle cancellations and pregnancy rates. Results A significant increase in number of mature and fertilized eggs was observed in women over 40 years of age using low dose hCG in addition to recFSH. The estradiol level was significantly higher on the day of hCG administration and the serum level of FSH on cycle day 7 and on the day of hCG administration were lower. Conclusion Addition of low dose hCG to recFSH compared with recFSH alone significantly modified cycle characteristics in patients >/= 40 years and could be of potential benefit for IVF cycles in older infertile women.